The study of EGFR-ligand complex electron property relationship with biological activity. Issue 1 (2nd January 2022) - Pathak, Prateek; Naumovich, Vladislav; Grishina, Maria; Potemkin, Vladimir
Abstract: The present investigation grounded on estimation of electron properties of the structures of EGFR proteins-ligand complexes using our laboratory-developed methodology AlteQ approach, which describes the molecular electron density of the complex in space for a certain point in three-dimensional coordinates. Briefly, the system embodies molecular electron density as a sum of Slater's type atomic increments of the molecular system. Further, using this methodology, we calculated different electron characteristics of selected EGFR protein-ligand complexes and established the relationship between different electron properties with their experimental pharmacological activity value (pIC50 ). The study suggested that EGFR inhibitory activity has higher correlation with intermolecular contacts of H with pi-system of aromatic ring between protein and ligands. Therefore, this created model has impact to identify and design potential ligands against EGFR in anticancer drug discovery. Communicated by Ramaswamy H. Sarma Graphical Abstract: UF0001